Adaptive Scheduling and Routing Scheme for Delay Guarantee in Wireless Sensor Networks - Yan Sun; Cong Chen; Hong Luo (International Journal of Distributed Sensor Networks, 2013)
In wireless sensor networks (WSNs), periodical sleeping scheme on sensor nodes is an effective way to save energy. However, it will hinder the capability of the network to provide real-time data reporting due to relay node being sleep. Motivated by this, we propose an adaptive scheduling and routing scheme for guaranteeing dynamic end-to-end delay requirement while minimizing the energy consumption. First of all, we utilize an optimal wake-up scheduling algorithm to achieve the initial wake-up schedules and routes and design an adaptive adjustment algorithm. When the end-to-end delay requirement of a region changes, our proposed adaptive adjustment algorithm can locally adjust the wake-up schedules or the routing tables of the nodes which are the nearest ones to the source node, so as to minimize energy consumption and the impact on other regions while guaranteeing the new end-to-end delay requirement of the region. Through experiments in a real wireless sensor network and extensive simulations, we can get that the proposed scheme can conserve at least 20% energy consumption comparing to other existing adjustment algorithms, and its performance approaches that of the optimal solution.